Determining levels of cryptic diversity within the endemic frog genera, Indirana and Walkerana, of the Western Ghats, India - Ramesh, Vijay (PLoS One, 2020)
A large number of species in the tropics are awaiting discovery, many due to their cryptic morphology ie. lack of discernable morphological difference. We explored the presence of cryptic lineages within the frog genera, Indirana and Walkerana, which are endemic to the Western Ghats of Peninsular India. By reconstructing a phylogeny using 5 genes and robust geographic sampling, we delimited 19 lineages along a population—species continuum, using multiple criteria including haplotype clusters, genetic distance, morphological distinctness, and geographical separation. Of these 19 lineages, 14 belonged to the genus Indirana and 5 to the genus Walkerana. Divergence dating analyses revealed that the clade comprising Indirana and Walkerana began diversifying around 71 mya and the most recent common ancestor of Indirana and Walkerana split around 43 mya. We tested for the presence of cryptic lineages by examining the relationship between genetic and morphological divergence among related pairs within a pool of 15 lineages. The pairs showed strong morphological conservatism across varying levels of genetic divergence. Our results highlight the prevalence of morphologically cryptic lineages in these ancient endemic clades of the Western Ghats. This emphasizes the significance of other axes, such as geography, in species delimitation. With increasing threats to amphibian habitats, it is imperative that cryptic lineages are identified so that appropriate conservation measures can be implemented.